Cry1 expression during postnatal development is critical for the establishment of normal circadian period - Schirmer, Aaron E.; Kumar, Vivek; Schook, Andrew; Song, Eun Joo; Marshall, Michael S.; Takahashi, Joseph S. (Frontiers in Neuroscience, 2023)
The mammalian circadian system generates an approximate 24-h rhythm through a complex autoregulatory feedback loop. Four genes, Period1 (Per1), Period2 (Per2), Cryptochrome1 (Cry1), and Cryptochrome2 (Cry2), regulate the negative feedback within this loop. Although these proteins have distinct roles within the core circadian mechanism, their individual functions are poorly understood. Here, we used a tetracycline trans-activator system (tTA) to examine the role of transcriptional oscillations in Cry1 and Cry2 in the persistence of circadian activity rhythms. We demonstrate that rhythmic Cry1 expression is an important regulator of circadian period. We then define a critical period from birth to postnatal day 45 (PN45) where the level of Cry1 expression is critical for setting the endogenous free running period in the adult animal. Moreover, we show that, although rhythmic Cry1 expression is important, in animals with disrupted circadian rhythms overexpression of Cry1 is sufficient to restore normal behavioral periodicity. These findings provide new insights into the roles of the Cryptochrome proteins in circadian rhythmicity and further our understanding of the mammalian circadian clock.